2021
DOI: 10.1002/jcp.30290
|View full text |Cite
|
Sign up to set email alerts
|

Chemerin located in bone marrow promotes osteogenic differentiation and bone formation via Akt/Gsk3β/β‐catenin axis in mice

Abstract: Chemerin, a secreted protein mainly produced by adipocytes and hepatocytes, plays a variety of roles in endocrine or paracrine signaling. As reported in human epidemiology, chemerin was correlated with osteoporosis. And the previous in vitro study found that chemerin knockdown promoted osteogenesis and inhibited adipogenesis. However, the function of chemerin in bone metabolism and the underlying mechanism remains unclear. In this study, we uncovered the in vivo function of chemerin in bone homeostasis. We dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 37 publications
(44 reference statements)
1
14
2
Order By: Relevance
“…Previous studies have reported that treatment with chemerin promoted osteoclastogenesis of hematopoietic stem cells (HSCs) in vitro [ [13] , 20 ], and increased bone resorption activity in mature osteoclasts [ 14 ]. Other investigators using chemerin or CMKLR1 knockout mice revealed that chemerin or CMKLR1 deficiency enhanced osteoclastic bone resorption and bone loss [ 9 , 19 ]. The cause for this discrepancy has not yet been identified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported that treatment with chemerin promoted osteoclastogenesis of hematopoietic stem cells (HSCs) in vitro [ [13] , 20 ], and increased bone resorption activity in mature osteoclasts [ 14 ]. Other investigators using chemerin or CMKLR1 knockout mice revealed that chemerin or CMKLR1 deficiency enhanced osteoclastic bone resorption and bone loss [ 9 , 19 ]. The cause for this discrepancy has not yet been identified.…”
Section: Discussionmentioning
confidence: 99%
“…While this paper was in revision, another report was published indicating that chemerin deficiency decreased osteogenesis and bone mass [ 9 ]. Although both studies highlight the effects of chemerin on bone metabolism, the two reports differ in the proposed effects of chemerin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoporotic skeleton correlates with the development of obesity [32], excess glucocorticoid [33], and estrogen deficiency [34]-mediated marrow fat and visceral adipose accumulation. The molecular mechanism by which osteoporotic bone tissue dysregulates systemic adipose development warrants investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Increase in adipogenesis at the expense of osteoblastogenesis (2), although animal models show osteogenic differentiation and bone formation (99).…”
Section: Chemerin Admentioning
confidence: 99%